Influência no comportamento mecânico do concreto com a utilização de microfibras de polipropileno para redução do efeito de retração: um estudo realizado em Belém do Pará - CUNHA, Wictor Alencar (Universidade Federal do Pará, 2024)
Seeking to mitigate the effect of concrete shrinkage, the influence on the mechanical behavior of concrete reinforced with polypropylene microfibers was studied in this study. In the experimental program, 15 (fifteen) study series were produced: one reference without the addition of polypropylene microfiber for each w/c ratio studied, totaling 3 series; and another 12 (twelve) series with the following characteristics: addition of 0.6% and 1.0% of microfiber content varying the length in 12 mm and 25 mm, the w/c ratios being studied with values of 0.45 ; 0.55 and 0.65. Tests were carried out in the fresh state of the concrete to evaluate consistency and workability; and in the hardened state to evaluate compressive strength, flexural traction and modulus of elasticity with age of the specimens at 7 and 28 days; and dimensional variation with age of 48h, 7 and 28 days. The results obtained were studied through analysis of variance (ANOVA) and the Tukey test to determine the statistical significance of the responses found. It was concluded that the optimum content of addition of polypropylene microfiber to concrete was 1.0% with fibers of 12 mm length and w/c ratio=0.55.